2012
DOI: 10.1351/pac-con-11-07-22
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of toxic and essential elements in Lebanese bread

Abstract: Concentrations of 20 minor, trace, and ultratrace elements relevant to human health (Ag, Al, As, Cd, Co, Cr, Cu, Fe, Hg, Li, Mn, Mo, Ni, Pb, Sb, Se, Si, Sn, V, and Zn) were determined in three varieties of Lebanese bread (white and brown double loaf bread, Saj bread) sampled at five geographical regions (Grand Beirut, South of Lebanon, North of Lebanon, Mount of Lebanon, and Beka’a) during the wet and dry seasons. The analyses were carried out by double-focusing sector-field inductively coupled plasma-mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…Also, previous studies involving 10 types of Polish bread showed an identical relationship [ 36 ]. Similarly, Khouzam et al [ 37 ] demonstrated that in Lebanese bread, the relationship between the content of microelements can be represented as Fe > Mn > Zn > Cu. Their values were 1.7–6 mg Cu, 8.2–40.9 mg Zn, 7.5–58.7 mg Mn, and 15.7–59.4 mg Fe per 1 kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Also, previous studies involving 10 types of Polish bread showed an identical relationship [ 36 ]. Similarly, Khouzam et al [ 37 ] demonstrated that in Lebanese bread, the relationship between the content of microelements can be represented as Fe > Mn > Zn > Cu. Their values were 1.7–6 mg Cu, 8.2–40.9 mg Zn, 7.5–58.7 mg Mn, and 15.7–59.4 mg Fe per 1 kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Bread is a source of energy and minerals, some of them being essential for the body. Essential minerals found in Lebanese bread are Cu, Fe, Mn, Zn, and Se which account for 36%, 25%, 30%, 22%, and 32% of respective recommended dietary allowance (RDA) values given for these elements [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Egypt, Iran, South Africa, Nigeria, and Portugal determined TEs contents in bread [18,19,20,21,22]. In Lebanon, Bou Khouzam and co-authors [1] determined the contents of 20 elements in three varieties of Lebanese bread (i.e., white, brown pita, and Saj bread) throughout the country during the wet and dry seasons. Toxic elements such as Cd and Pb were below maximum levels set by the Lebanese regulatory agency, (The Lebanese Standards Institution—Libnor) [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations